Improving the Competence of the Gymnastics Trainer of the Healthy Heart Club in Surakarta about Fitness Exercise Exercise Program - Riyadi, Slamet; Waluyo, Waluyo; Utomo, Tri Aprilijanto; Sarjoko, Sarjoko (Universitas Sebelas Maret, 2021)
Community service is the implementation of a fitness exercise program for the Surakarta Healthy Heart Club gymnastics trainer during the covid-19 pandemic. This activity was carried out considering the important role of a healthy heart exercise trainer in an effort to nourish and improve people's fitness so that they have good endurance and avoid transmission of the corona virus. A trainer must have sufficient competence, knowledge and training skills to successfully carry out the vision and mission of the Indonesian Heart Foundation. In connection with the above, the purpose of this activity is to equip trainers with competence, knowledge and training skills for trainers of healthy heart club gymnastics in Surakarta. The materials provided to the gymnastics trainers include training in the preparation of exercise programs, fitness exercise materials, mentoring in the implementation of training during the COVID-19 pandemic and evaluation of physical fitness. The methods used in this activity are: 1) Exposure and discussion of physical fitness material, 2) Demonstration and practice for skills material, namely the practice of compiling an exercise program, practicing fitness and coaching practice with mentoring during P2M. This material is important and urgent to be given to the coach of the Surakarta Healthy Heart Club considering the current situation and conditions, namely the increasingly outbreak of the Covid-19 pandemic in Surakarta and its surroundings.